Efficacy, safety and factors associated with disease progression in patients with unresectable (stage III) or distant metastatic (stage IV) BRAF V600-mutant melanoma: An open label, non-randomized, phase IIIb study of trametinib in combination with dabrafenib. (September 2021) - Saiag, Philippe; Robert, Caroline; Grob, Jean-Jacques; Mortier, Laurent; Dereure, Olivier; Lebbe, Céleste; Mansard, Sandrine; Grange, Florent; Neidhardt, Eve-Marie; Lesimple, Thierry; Machet, Laurent; Bedane, Christophe; et al.
Abstract: Background: BRAF and MEK inhibitors combination, including dabrafenib (D) and trametinib (T) have transformed the treatment of BRAF V600 -mutant advanced melanoma patients, including patients with brain metastasis (BM). In a large phase IIIb, single-arm, open-label, multicenter French study, we assessed safety, response to treatment, progression-free survival (PFS) and factors associated with progression, and stratified the population into risk groups. Methods: Patients with unresectable, advanced, BRAF V600 -mutant melanoma were included, including those with the presence of BM, Eastern Cooperative Oncology Group Performance Status (ECOG PS) ≤2, elevated lactate dehydrogenase (LDH) or previous melanoma treatments. Responses were determined locally, without central review. PFS was estimated using the Kaplan–Meier analysis and modelled with multivariate Cox model. Risk subgroups were identified using a regression tree analysis. Results: Between March 2015 and November 2016, 856 patients received at least one D + T dose. Overall, 92% had stage IV melanoma, 38% ECOG PS ≥1, 32% BM and 37.5% elevated LDH. Median PFS was 8.02 months (95% confidence interval [CI] 7.33–8.77). Significant factors associated with lower PFS were ECOG PS ≥1, elevated LDH, ≥3 metastatic sites and presence of BM. Patients with <3 metastatic sites, ECOG = 0 and no BM had the highest probability of PFS at 6 months (83%, 95% CI 76–87) and 12 months (56%, 95% CI 47–64), respectively. Conclusions: This is the largest prospective study in advanced BRAF V600 -mutant melanoma patients treated with D + T, conducted in conditions close to 'real-world practice'. We confirm previous findings that LDH, ECOG PS and ≥3 metastatic sites are associated with shorter PFS, but the real-world setting introduces BM as a major prognostic factor. Highlights: This is the largest close to real-word study on BRAF V600-mutant melanoma patients. The study included the largest population of melanoma patients with brain metastases. The results confirm the clinical activity of trametinib associated to dabrafenib. LDH, ECOG, number of metastatic sites and presence of brain metastases associated with PFS.